Research waste and inefficiency in cardiovascular prediction rule development: exploration of causes and implications - Ban, J-W (2021)
Background: Research waste and inefficiency occur when research studies do not contribute to the decisions of patients, clinicians, and policymakers. In this thesis, I examine research waste and inefficiency throughout the stages of cardiovascular clinical prediction rule (CPRs) development and explore their causes and implications.